Pengetahuan tentang penyakit hepatitis B dengan perilaku pemeriksaan HBsAg pada ibu hamil di Puskesmas - Surmiasih, S; Aprida, Hernovi; Hardono, Hardono; Putri, Riska Hediya (Universitas Aisyah Pringsewu (UAP) Lampung, 2020)
Hepatitis B is a liver disease that can be chronic and can cause cirrhosis. Pregnant women infected with hepatitis B can transmit the infection vertically to the fetus they were carrying during labor and immediately after delivery in Indonesia, there were 1,017,290 people with hepatitis out of this number 506,576 were female patients. Risks obtained by pregnant women who are infected with HBV can include abortion, preterm labor, and bleeding. The purpose of this study was to determine the level of knowledge about hepatitis B and HBsAg examination behavior in pregnant women at Puskesmas Kasui Kabupaten Way Kanan. The type of this research was quantitative descriptive, with a cross-sectional approach. Total sampling. Analysis of using descriptive statistical tests. The results showed a level of knowledge about hepatitis B with less understanding of 40 percent and HBsAg examination behavior in pregnant women by 54.3 percent. It is expected that the results of this study can improve services to pregnant women in providing counseling about hepatitis B and HBsAg examination for early detection by conducting HBsAg Rapid Diagnostic Test (RDT) so that they can handle early to prevent transmission of the virus from mother to baby.